Feasibility of prehospital identification of non-ST-elevation myocardial infarction by ECG, troponin and echocardiography. Issue 9 (21st January 2022) - Jacobsen, Lars; Grenne, Bjørnar; Olsen, Roy Bjørkholt; Jortveit, Jarle
Abstract : Background: Prehospital identification and selection of treatment strategy in patients with suspected non-ST-elevation myocardial infarction (NSTEMI) is challenging. The aim of this study was to evaluate the feasibility and diagnostic accuracy of prehospital ECG, troponin T (TnT) and transthoracic echocardiography (TTE) acquired by paramedics in early identification of NSTEMI. Methods: Consecutive patients requesting an ambulance from Sorlandet Hospital, Norway due to chest pain between November 2017 and January 2020 were screened for inclusion in the study. One ambulance was equipped with ECG recorder, point-of-care TnT test and TTE scanner, and six paramedics were given necessary training. ECG, TnT result and TTE images were acquired prehospitally and transferred to an in-hospital cardiologist. NSTEMI was suspected in patients with ischaemic ECG changes, elevated TnT or myocardial regional wall motion abnormalities (RWMA) at TTE. Results: A total of 253 patients were included in the study. ECG was interpretable by cardiologists in 243 (96%), TnT in 238 (94%) and TTE images in 240 (95%) patients. NSTEMI was the discharge diagnosis in 22 (9%) of these patients. Four (18%) patients with NSTEMI had ischaemic ECG changes, elevated TnT and RWMA at TTE. Eight (36%) patients with NSTEMI had positive findings at two of the diagnostic methods, six (27%) patients had positive findings at one, and four (18%) patients had no positive findings in any of the diagnostic methods. In three patients (14%) with NSTEMI, RWMA was the only positive test. The negative and positive predictive values for RWMA were 42% and 96%, respectively. Conclusions: Prehospital acquisition of ECG, TnT and interpretable TTE images by paramedics were feasible in most patients with chest pain. Based on these examinations, it was possible to identify the majority of cases with NSTEMI prehospitally and admit the patients directly to a hospital with facilities for percutaneous coronary intervention (PCI) for further treatment. Trial registration number: NCT04223986 .